Factors Affecting the Adoption of mHealth Services among Young Citizen: A Structural Equation Modeling (SEM) Approach - Hoque, Md. Rakibul; Karim, Mohammad Rezaul; Amin, Mohammad Bin (Asian Business Review, 2015)
In Bangladesh, nearly everyone has access to a mobile phone and it is increasingly affordable and widespread in all clusters of people have significant impact to extend social relations. The telecom is one of the rapidly growing industries in Bangladesh. Mobile phone is playing a vary significance role with pervasive services. Dissemination of health related information to the general people was a great challenge for this highly populated country, but this problem is going to be erased by application of mobile phone in this regards. In this study attempted to determine and measure the various usages of mobile phone in Bangladesh among the young age group (patients) how they use Mobile phones to solve health related problem. Technology Acceptance Model (TAM) is used as the theoretical underpin to conduct this study. A questionnaire survey method was used to collect data from respondents in different public and private universities of Bangladesh. The data were analyzed using the Partial Least Squire (PLS) method, a statistical analysis technique based on structural Equation Model (SEM). Findings revealed that perceived usefulness (p < 0.05) positively predicted the intention to use mHealth services, while perceived ease of use (p > 0.05) was identified as a less significant factor in the mHealth adoption in Bangladesh. The findings from the study can serve as input to promote citizen’s use of mobile phone for better self-management of health.
Keywords: mHealth; Bangladesh; Technology Acceptance Model (TAM)